Particulate matter emission in agricultural biomass residue combustion - M.G. Nugraha; A. Sharfan; V.S.Y. Prakoso; M. Hidayat; H. Saptoadi (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Agriculture significantly contributes to global economies, yet it concurrently generates waste in the form of crop residues. Conventional waste disposal methods, such as open burning, contribute to atmospheric particulate emissions, impacting air quality regionally and potentially globally. Exposure to these pollutants poses substantial risks to human health, including respiratory illnesses, cardiovascular diseases, and premature mortality. This study aims to assess the environmental implications of biomass waste combustion in Yogyakarta, Indonesia. Additionally, the study aims to investigate potential enhancements in biomass burning practices through experimental campaigns conducted in both open and closed burning conditions.METHODS: The study evaluates Yogyakarta's regional air quality using data from the Meteorology, Climatology, and Geophysical Agency for the period spanning from 2020 to 2022. Emission factors from open and closed burning practices are assessed using an experimental furnace equipped with real-time combustion parameters monitoring, including temperature, particulate matter concentration, and oxygen and carbon dioxide levels. The openburning experiments involve various combustion conditions for bagasse, leaf litter, and rice straw, encompassing variations in ignition location, initial mass, and air supply methods. Closed burning experiments explore variations in reloading frequency, air-fuel ratio, and air staging.FINDINGS: Yogyakarta's air quality assessment involves comparing rice harvest trends with atmospheric particulate matter concentrations during 2020-2022. Open burning practices in Yogyakarta exhibit a correlation with heightened rainfall, which in turn leads to higher emissions from April to August due to reduced rain frequency. Experimental campaigns have revealed that open burning practices result in a significant amount of emissions, ranging from 3 to 29 grams of particulate matter per kilogram of biomass.. Meanwhile, the utilization of closed combustion systems has been demonstrated to decrease the emission factor within the range of 0.37 to 1.98 grams of particulate matter per kilogram of biomass. This highlights the importance of operating conditions altering particulate emissions. Moreover, the emission reduction by factor nine, emphasizing the efficacy of controlled combustion techniques in comparison to open burning methods, in mitigating particulate emissions.CONCLUSION: The study identifies that greater initial biomass mass, mid-ignition, and natural airflow contribute to lower emissions in open burning practices. o achieve optimal closed combustion conditions, it is recommended to reload biomass more frequently with100 percent excess air allocation, distributing 30 percent to primary air and 70 percent to secondary air. These findings not only propose better practices for disposing of agricultural waste and minimizing air pollution but also emphasize the potential of utilizing biomass waste for energy conversion.